The Potential impact of Intermodalism, mobility, Safety and Security on Sustainability of Multimodal Transportation in Suez Canal Hub - Amr Mohammad Mashaly (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Abstract The Suez Canal Hub Development is highly expected to influence almost all of the transportation regular routes when it comes to global trade. It is known that most of the shipments that go through Suez Canal, competitors take place from Asia and the United States. According to the East Coast, it consists of U.S. Intermodal System and the Panama Canal as well. However, this cannot deny that the Suez Canal is an efficient route. The reason is that it can reach the maximum expected capacity. Particularly, it is safe to state that the Suez Canal route is having a real competition with Panama Canal supporting the South and Southeast of Asia and the U.S. The main objective of this paper is to expose and draw a comparison and analysis between the Suez Canal and the Panama Canal. Moreover, it investigates the impact of Secure Transportation on Sustainability of Multimodal Transportation, intermodalism, safety and mobility. According to the findings of this study, it has shown and confirmed that safety and security are the main and most essential influencing parameters related to Sustainability of Multimodal Transportation in Suez Canal Hub.